Advertising and satirical culture in the Romantic period - Strachan, John (Cambridge University Press, 2007)
Advertising, which developed in the late eighteenth century as an increasingly sophisticated and widespread form of brand marketing, would seem a separate world from that of the 'literature' of its time. Yet satirists and parodists were influenced by and responded to advertising, while copywriters borrowed from the wider literary culture, especially through poetical advertisements and comic imitation. This 2007 study to pays sustained attention to the cultural resonance and literary influences of advertising in the late eighteenth and early nineteenth centuries. John Strachan addresses the many ways in which literary figures including George Crabbe, Lord Byron and Charles Dickens responded to the commercial culture around them. With its many fascinating examples of contemporary advertisements read against literary texts, this study combines an intriguing approach to the literary culture of the day with an examination of the cultural impact of its commercial language.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Englisch; Literatur; Werbegrafik; Satire